Tourist’s Perceived Risk and Image of the Destinations Prone to Natural Disasters: The Case of Bali and Yogyakarta, Indonesia - Erda Rindrasih (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
Tourism has emerged as one of the largest and most rapidly growing economic sectors in the world. Nevertheless, many tourist destinations have been periodically confronted by natural disasters that threaten their survival as an industry by negatively impacting their image and safety perception. This research assessed tourists’ perception of the risk and images of a destination that is considered prone to natural disasters, by surveying 537 tourists in Yogyakarta and Bali. This study contributes to the debate on tourism development issues related to negative perceptions and images that have discouraged prospective tourists from visiting affected destinations. The results of the survey indicated that the occurrence of past disasters did not strongly influence tourists’ decision to visit Indonesia. Instead, the creation of the destination image was informed more by its current situation, and it is these current factors that may encourage or discourage potential tourists. These findings should signal to tourism planners that while environmental disasters are unavoidable, post-disaster rehabilitation of a destination’s image would significantly increase its chances of rebounding quickly.